The Sciences : An Integrated Approach - Trefil, James and Hazen, Robert M. (New York John Wiley & Sons., 2000)
Pick up any newspaper and there are articles that relate to science (genetic engineering, cancer research, etc.). This book takes an integrated approach to science to educate readers so they understand the issues and can participate in the debates that will only grow over time. Provides readers with a sound overview of the principles of sciences required to make decisions related to issues such as healthcare, technology, the environment, alternative energy sources, nutrition and medical research. Also examines the social or philosophical issues related to science, such as nuclear waste disposal, the human genome project, and priorities in medical research. It will also have increased coverage of biotechnology and biological examples will be added when relevant. This edition features relevant web sites behind each chapter and all new science news articles to keep current.
Include Appedices, Glosssary, Index and colored Illustrations.
Keywords: Science--Study and Teaching (Higher) -- United States